Tinjauan Literatur Sistematis Terhadap Dampak Karakteristik Dewan Dan Struktur Kepemilikan Pada Manajemen Laba - Saputri, Irma Rezki (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
This study conducts a systematic literature review on the impact of board characteristics and ownership structure on earnings management practices by analyzing 25 empirical studies in Indonesia during 2020-2025. Thematic analysis method was applied to identify relationship patterns and inconsistencies across industry contexts. Results indicate that board independence, board size have diverse influences depending on firm characteristics. Institutional ownership structure demonstrates dual effects as both monitoring mechanism and facilitator of opportunistic practices. Foreign ownership proves effective in reducing earnings manipulation. Complex interactions among governance mechanisms generate synergistic effects. Heterogeneity of findings indicates the importance of contextual approaches in governance policy design. This research contributes theoretically through comprehensive literature synthesis and provides practical implications for regulators and practitioners in enhancing financial reporting quality.